2014
DOI: 10.1371/journal.pone.0115698
|View full text |Cite
|
Sign up to set email alerts
|

Selective Calcium Sensitivity in Immature Glioma Cancer Stem Cells

Abstract: Tumor-initiating cells are a subpopulation in aggressive cancers that exhibit traits shared with stem cells, including the ability to self-renew and differentiate, commonly referred to as stemness. In addition, such cells are resistant to chemo- and radiation therapy posing a therapeutic challenge. To uncover stemness-associated functions in glioma-initiating cells (GICs), transcriptome profiles were compared to neural stem cells (NSCs) and gene ontology analysis identified an enrichment of Ca2+ signaling gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Hence, there is an urgent need for therapies that would specifically target this tumor cell population, sparing normal cells. In line with other researchers (8,9), we recently showed that tumor-initiating cells are sensitive to disturbed Ca 2þ homeostasis (10), making ion channels appealing targets in GICs. Noteworthy, ion channels are also known to be dysregulated during cancer formation and progression (11).…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Hence, there is an urgent need for therapies that would specifically target this tumor cell population, sparing normal cells. In line with other researchers (8,9), we recently showed that tumor-initiating cells are sensitive to disturbed Ca 2þ homeostasis (10), making ion channels appealing targets in GICs. Noteworthy, ion channels are also known to be dysregulated during cancer formation and progression (11).…”
Section: Introductionsupporting
confidence: 85%
“…All GIC lines are GBM patient-derived primary cell lines grown as monolayer cultures on laminin in neural stem cell culture media, as described previously (2,10,15,16). Cells were used for experiments between passages 15 and 30, at least one passage after thawing.…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Disturbances in chloride balance may play a role as well, secondary to changes in chloride co-transporters, suggesting accompanying changes in GABA metabolism and chloride transport (Huberfeld et al, 2007; Pallud et al, 2013). Besides, glutamergic stimulation of NMDA and AMPA receptors may activate intracellular mTOR, AKT, and MAPK signaling pathways, contributing both to cell growth and to epileptogenesis (Wee et al, 2014). …”
Section: Incidence Of Epilepsy In Brain Tumor Patientsmentioning
confidence: 99%
“…Cancer stem cells are very aggressive as they are highly invasive, mobile, resistant to radiation and chemotherapy, and have the capacity to self-renew (Oh et al, 2012). Recent studies have shown that calcium (Ca 21 ) channel signaling controls a variety of stem cells and cancer cell lines functions, such as proliferation and migration (Wee et al, 2014). Moreover, Ca 21 channel interference was able to drive liver tumor-initiating cells into apoptosis (Zhao et al, 2013) and glioma stem-like cells were more sensitive to Ca 21 disturbances compared with more mature differentiated glioma cells (Wee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%